Career planning and anchor: a study with discents from the Administration course of the University of Pernambuco - campus Salgueiro (Research, Society and Development, 2021)
This research aims to analyze the relationship between career planning and management and the categories of career anchor according to the perception of students from the last period of the administration course at the University of Pernambuco (UPE), campus Salgueiro. The survey of data for the study was carried out through the application of questionnaires, which was adapted from Schein (1993) and was structured in two parts: (1) five questions per scale of agreement on the perception of undergraduate students in management regarding planning (2) Schein's Inventory, composed of forty scale questions, which aim to identify the career anchors of individuals among eight possible categories. After the analysis, it can be described that the results about the student’s knowledge regarding personal career planning, denote the importance of the existence of a discipline or extension courses with emphasis on the theme Planning and Career Management for the Administration course. In the second part of the study, career anchors with the highest and lowest scores were identified, and finally the analysis of the anchor and gender. In general, it is observed that the three main anchors are autonomy and independence (AI), a safety and stability anchor (SE) and a lifestyle anchor (EV), these results demonstrate that students tend to be concerned with the balance and integration of your personal and professional needs. The results also demonstrate that students seek to change from a traditional profile to one more in tune with current trends.